The Promises and Pitfalls of Moral Formation in American Civil Religion - Salter, Richard C. (Silliman Journal, 2022)
Service-learning and community service seem like unambiguously positive things to do. This article argues that, while that is often the case, there can also be unintended consequences of service that may undermine the very goals that service intends to achieve. The article focuses on the United States and the role that service plays in American Civil Religion. The article traces out a short history of secular non-military history, its relationship to other aspects of US culture, and its emergence in recent years as a key part of character formation in American Civil Religion. The author suggests that traditional religions have avoided the pitfalls of an over emphasis on works with a parallel emphasis on spirituality, and the article asks whether such service in a secular context can avoid the unintended consequences associated with it.